Penerapan Metode Demonstrasi Untuk Meningkatkan Prestasi Belajar Matematika Siswa Kelas I SDN 002 Ujung Batu Kabupaten Rokan Hulu Tahun Ajaran 2014/2015 - Maria Ulfa (STKIP Rokania Pasir Pangaraian, 2018)
This classroom action research was conducted in Ujung Batu SDN 002 Rokan Hulu District in class I 2014/2015 school year. The action was taken by applying the demonstration method to improve students' mathematics learning achievement. Demostration learning method is a learning method that can improve students' thinking ability to solve the problems they face. By using the demonstration method, student learning outcomes each cycle change and increase. This is proven by the achievement of the results of the pre-cycle test, the average percentage of only 57% and at the end of the second cycle reached 90%. The application of the demonstration method can improve the competence of grade 1 students at Ujung Batu 002 SDN Rokan Hulu Regency